Employability for music graduates: Malaysian educational reform and the focus on generic skills - Ghazali, G.; Bennett, Dawn (SAGE publishers, 2017)
In Malaysia, the demand for employable higher education graduates has resulted in a national strategy that outlines desirable graduate attributes including “hard,” discipline-specific skills and “soft,” generic skills. As a result, music programs are under pressure to become more relevant to the conditions and characteristics of the industry. This article presents an overview of the whole-of-education trends in Malaysia and then reports empirical data from eight Malaysian music professionals, all higher education music graduates, who described their pre-sage, transitional and career experiences. Participants emphasized that hard and soft skills are equally important dimensions of graduate employability, which supports the heightened national focus on generic skills. However, participants’ focus was not on the skills per se; rather, they stressed the need for students to apply and reflect upon their development of skills during their studies. The article aligns this thinking with the Malaysian strategy and a commonly used employability framework to illustrate the soft skills that might be required of music graduates.